2018
DOI: 10.1097/md.0000000000010152
|View full text |Cite
|
Sign up to set email alerts
|

Identification of biomarkers of venous thromboembolism by bioinformatics analyses

Abstract: Venous thromboembolism (VTE) is a common vascular disease and a major cause of mortality. This study intended to explore the biomarkers associated with VTE by bioinformatics analyses.Based on Gene Expression Omnibus (GEO) database, the GSE19151 expression profile data were downloaded. The differentially expressed genes (DEGs) between single VTE (sVTE)/recurrent VTE (rVTE) and control were identified. Then, pathway enrichment analysis of DEGs were performed, followed by protein–protein interaction (PPI) network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…It has been indicated that combination of a microarray technology with a bioinformatics analysis method could comprehensively analyze the expression changes of genes in VTE patients. 6 However, there are no bioinformatics analyses published on the link between differentially expressed genes (DEGs) and differentially expressed miRNAs (DEMs) in VTE.…”
Section: Introductionmentioning
confidence: 99%
“…It has been indicated that combination of a microarray technology with a bioinformatics analysis method could comprehensively analyze the expression changes of genes in VTE patients. 6 However, there are no bioinformatics analyses published on the link between differentially expressed genes (DEGs) and differentially expressed miRNAs (DEMs) in VTE.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that TP53 is involved in hemostasis and trombosis associated pathway [ 27 ]. TP53 is a potential diagnosis and treatment target for venous thromboembolism [ 28 ]. Our result indicated that down‐regulated hsa‐miR‐150‐5p could play an important role in the coagulation process of deep venous thrombosis via regulating PRKCA, SP1 and TP53.…”
Section: Discussionmentioning
confidence: 99%
“…Several DEGs encoding ribosomal proteins were also identified and enriched in module 1. The ribosomal family proteins are upregulated in the plasma of VTE patients 71,72 , and are known to trigger venous thrombus formation in aged mice via p53 activation 73 . Furthermore, ribosomal proteins are also detected in circulating platelets and are associated with VTE 74,75 .…”
Section: Discussionmentioning
confidence: 99%